Water-absorbent resin composition and method for producing water-absorbent resin

A highly absorbent resin with high water absorption, high dryness and appropriate biodegradability was prepared by free radical polymerization of hydrolyzed collagen and aqueous solution of carboxylic acid monomers. This solved the problems of environmental pollution and low degradation efficiency of existing absorbent resins and can be applied in multiple industrial and daily life fields.

CN119306901APending Publication Date: 2025-01-14TAIWAN SOKOU INDS KOFUN YUUGENKOUSHI
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310997470.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-12
Filing Date
2023-08-09
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Existing absorbent resins suffer from air pollution and low biodegradability during waste disposal, and existing improvement methods suffer from high production costs, poor performance, or unpleasant consumer perception.

Method used

Using hydrolyzed collagen as raw material, a water-absorbing resin with high water absorption, high dryness and appropriate biodegradability is prepared through free radical polymerization reaction of aqueous solution containing carboxylic acid monomers, crosslinking agent and polymerization initiator.

Benefits of technology

This invention achieves a balance between high absorbency and dryness of the absorbent resin, along with good biodegradability, making it suitable for personal hygiene products, agriculture, horticulture, construction, petroleum industry, cable manufacturing, medicine, and entertainment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to a water-absorbent resin composition and a manufacturing method of water-absorbent resin. The water-absorbent resin composition comprises a carboxylic acid group-containing monomer aqueous solution, hydrolyzed collagen, a cross-linking agent and a polymerization initiator. Since the water-absorbent resin composition has a specific use amount and molecular weight of hydrolyzed collagen, the prepared water-absorbent resin can have high water absorption, high dryness and proper biodegradability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a water-absorbent resin composition, and more particularly to a water-absorbent resin composition comprising hydrolyzed collagen and having high water absorption, high dryness and appropriate biodegradability. Background Art

[0002] Water-absorbent resin is a polymer material that can absorb and retain liquids. The mass of liquid that can be absorbed can be 50 to 500 times, or more, the weight of the water-absorbent resin itself. Because of its good water absorption, water-absorbent resin can be widely used in personal hygiene products (such as baby diapers, female physiological products, disposable wipes and / or adult diapers), as well as in agriculture and horticulture (such as water retention agents), construction (such as anti-dew condensation agents), petroleum industry (such as dewatering agents), cable manufacturing (such as waterproof coating agents), pharmaceutical industry (such as wound dressings) and entertainment industry (such as inflatable toys, artificial snow), etc.

[0003] The wide application of water-absorbent resins also creates waste problems. The existing treatment methods are incineration or landfilling. However, incineration will further cause pollution problems such as air pollution and carbon emissions; landfilling is limited by the low efficiency of biological degradation of water-absorbent resins, which will still cause a significant burden on the environment.

[0004] Therefore, biodegradable water-absorbent resins have become a new research direction. Among them, Japanese Patent Publication No. 1999-343339 discloses the use of water-absorbent resins produced by the reaction of poly-γ-glutamic acid and polyepoxide; US Patent Publication No. 2017 / 0002098 discloses the use of polysaccharide hydrogels; Chinese Publication Nos. 1410463 and 1846544 disclose the use of konjac flour, yacon and other biomaterials as crosslinking agents; Taiwan Invention Patent No. TWI432501B discloses the addition of unsaturated double bond compounds or epoxy resin compounds for polymerization.

[0005] Although the above methods are helpful for cleaning up waste water-absorbent resins, polysaccharide compounds not only have the disadvantage of complicated processing, but also the water-absorbent resins obtained are too soft and rotten after absorbing water, and have low performance, and cannot achieve the functions required by current sanitary products. Poly-γ-glutamic acid needs to be prepared by microbial culture, so it needs to be sterilized before use, which not only increases production costs but also makes the manufacturing process more complicated. Although water-absorbent resins using starch as copolymers have high biodegradability, starch is prone to yellowing during the heat treatment step, resulting in poor sensory perception for consumers. Although adding unsaturated double bond compounds or epoxy resin compounds for polymerization can increase the biodegradability of water-absorbent resins, if natural materials can be used, the correlation with petrochemical raw materials can be reduced.

[0006] Therefore, there is an urgent need for a water-absorbent resin with high water absorption, good dryness and appropriate biodegradability to solve the above problems. Summary of the invention

[0007] Therefore, one aspect of the present invention is to provide a water-absorbent resin composition comprising hydrolyzed collagen.

[0008] Another aspect of the present invention is to provide a method for producing a water-absorbent resin, comprising adding hydrolyzed collagen, so that the produced water-absorbent resin has high water absorption, high dryness and appropriate biodegradability.

[0009] According to the above aspect of the present invention, a water-absorbent resin composition is provided, comprising an aqueous solution of a carboxylic acid group-containing monomer, hydrolyzed collagen, a cross-linking agent, and a polymerization initiator. The neutralization rate of the aqueous solution of the carboxylic acid group-containing monomer is greater than or equal to 45 mol%, and the pH value of the aqueous solution of the carboxylic acid group-containing monomer is less than or equal to 7.0. Secondly, the above-mentioned polymerization initiator includes a thermal decomposition type initiator and / or a redox type initiator.

[0010] In one embodiment of the present invention, the molecular weight of the hydrolyzed collagen is greater than or equal to 1 KDa and less than 10 KDa.

[0011] In one embodiment of the present invention, based on 100 weight percent of the water-absorbent resin composition, the amount of the hydrolyzed collagen is 0.1 weight percent to 20 weight percent.

[0012] In one embodiment of the present invention, the water-absorbent resin composition may optionally include a surface treatment agent.

[0013] In one embodiment of the present invention, the hydrolyzed collagen is obtained by hydrolyzing fish scales with a hydrolyzing protease.

[0014] In one embodiment of the present invention, the hydrolytic protease is a serine endoprotease.

[0015] According to another aspect of the present invention, a method for producing a water-absorbent resin is provided, comprising a step of neutralizing a carboxylic acid group monomer aqueous solution with an alkaline compound to obtain a carboxylic acid group monomer aqueous solution, wherein the neutralization rate of the carboxylic acid group monomer aqueous solution is greater than or equal to 45 mol percent, and the pH value of the carboxylic acid group monomer aqueous solution is less than or equal to 7.0.

[0016] Next, a carboxylic acid group-containing monomer aqueous solution, hydrolyzed collagen, a cross-linking agent and a polymerization initiator are mixed to perform a free radical polymerization reaction, thereby obtaining a water-absorbent resin, wherein the hydrolyzed collagen is obtained by hydrolyzing fish scales with a hydrolyzing protease. Then, after the free radical polymerization reaction, a drying step is performed to obtain a water-absorbent resin.

[0017] In one embodiment of the present invention, the method for producing the water-absorbent resin may optionally include performing a surface cross-linking treatment on the water-absorbent resin.

[0018] In one embodiment of the present invention, the hydrolytic protease is a serine endoprotease.

[0019] In one embodiment of the present invention, the molecular weight of the hydrolyzed collagen is greater than or equal to 1 KDa and less than 10 KDa.

[0020] The water-absorbent resin composition and the method for producing the water-absorbent resin of the present invention, wherein the water-absorbent resin composition comprises hydrolyzed collagen, can produce a water-absorbent resin with high water absorption, high dryness and appropriate biodegradability. DETAILED DESCRIPTION

[0021] As mentioned above, the present invention provides a water-absorbent resin composition, which includes hydrolyzed collagen to obtain a water-absorbent resin with high water absorbency, high dryness and appropriate biodegradability, and further mixed with a fiber base material to obtain an absorbent body.

[0022] The "water absorption" described herein refers to the ability of a water-absorbent resin to absorb liquid. The liquid may be pure water or an aqueous solution. In some specific examples, the aqueous solution may include, but is not limited to, saline, urine, menstrual blood, soil water, or aqueous solutions in other application environments. It is worth noting that salts affect the water absorption of the water-absorbent resin, so the weight of the aqueous solution containing salts that can be absorbed by the water-absorbent resin is smaller than that of pure water. To simulate real-life usage, the water absorption of the water-absorbent resin can be evaluated using saline or synthetic urine.

[0023] In some embodiments, water absorption can be evaluated using absorption capacity (also known as free swell capacity, FSC), which is the ratio of the weight of liquid absorbed by the water-absorbent resin to the dry weight of the water-absorbent resin without applying external force to the water-absorbent resin.

[0024] In other embodiments, the water absorption can be evaluated when the water absorbent resin is subjected to an external force. In some specific examples, the water absorption can be evaluated using centrifuge retention capacity (CRC), which is the ratio of the weight of the liquid retained in the water absorbent resin after the water absorbent resin absorbs the liquid and is centrifuged to the dry weight of the water absorbent resin without absorbing the liquid.

[0025] In some embodiments, the water absorption can be evaluated by the absorption against pressure (AAP), which is the weight of the liquid absorbed by the water-absorbent resin relative to the dry weight of the water-absorbent resin without absorbing the liquid after the water-absorbent resin absorbs the liquid for a period of time under a certain pressure.

[0026] In some embodiments, water absorption can be evaluated using an absorption index under pressure, wherein the absorption index under pressure (index of AAP) is the ratio of the core shell absorption against pressure (CSAAP) to the absorption under pressure. The core shell absorption against pressure is evaluated in a similar manner to the absorption index under pressure, except that the absorption time of the core shell absorption against pressure is longer.

[0027] The "high water absorbency" described herein means that the water absorbent resin has an absorption rate greater than or equal to 50 g / g, a water absorbency under pressure greater than or equal to 15 g / g, preferably greater than or equal to 20 g / g, more preferably greater than or equal to 30 g / g, and an absorption index under pressure greater than or equal to 0.8. Experiments have confirmed that the water absorbent resin of the present invention has a water absorbency of 50 g / g to 65 g / g, a water absorbency under pressure of 20 g / g to 30 g / g, and an absorption index under pressure of greater than or equal to 0.8 and less than 0.9.

[0028] The "dryness" described herein refers to the difficulty of releasing liquid after the water-absorbent resin absorbs liquid. In some embodiments, the dryness can be evaluated by the rewet amount of the absorbent made of the water-absorbent resin, wherein the rewet amount is the weight of the liquid released after the absorbent absorbs liquid and is subjected to pressure. The "high dryness" described herein refers to the rewet amount being less than 5g. It has been experimentally confirmed that the rewet amount of the absorbent made of the water-absorbent resin of the present invention is less than 5g, such as: 0.1g to 2.0g, or 0.5g to 1.5g.

[0029] The "biodegradability" described herein refers to the ease with which microorganisms can degrade the water-absorbent resin. In some embodiments, the biodegradability can be evaluated by the colloid strength of the water-absorbent resin after treatment with L-ascorbic acid. It is worth noting that L-ascorbic acid or its salts can make the water-absorbent resin swell and crack, which helps to biodegrade the water-absorbent resin. However, L-ascorbic acid and its salts are also present in liquids such as urine, menstrual blood, and soil water. If the colloid strength of the water-absorbent resin after treatment with L-ascorbic acid is too low, the durability of the absorbent obtained is poor, so the biodegradability needs to be controlled within an appropriate range.

[0030] The "appropriate biodegradability" described herein means that the colloid strength of the water-absorbent resin after being treated with L-ascorbic acid for 3 hours is 100 g to 200 g, and the colloid strength after being treated with L-ascorbic acid for 24 hours is 50 g to 110 g. It has been experimentally confirmed that the colloid strength of the water-absorbent resin of the present invention after being treated with L-ascorbic acid for 3 hours is 100 g to 150 g, or 110 g to 135 g, and the colloid strength after being treated with L-ascorbic acid for 24 hours is 50 g to 80 g, or 50 g to 75 g.

[0031] In order to make the water-absorbent resin have high water absorption, high dryness and appropriate biodegradability, the present invention adds hydrolyzed collagen. Specifically, the water-absorbent resin composition includes an aqueous solution of a carboxylic acid group-containing monomer, hydrolyzed collagen, a crosslinking agent and a polymerization initiator.

[0032] The aqueous solution of carboxylic acid-containing monomers is prepared by dissolving carboxylic acid-containing monomer compounds in water and then using alkaline compounds to perform a neutralization step. Carboxylic acid-containing monomer compounds may include but are not limited to acrylic acid compounds, other suitable carboxylic acid-containing monomer compounds, or any mixture of the above compounds. In some specific examples, acrylic acid compounds may include but are not limited to acrylic acid, methacrylic acid, acrylic acid-2-carboxylic acid ethyl ester, methacrylic acid-2-carboxylic acid ethyl ester, methyl acrylate and / or ethyl acrylate. In some embodiments, carboxylic acid-containing monomer compounds may selectively include water-soluble monomers having other acid groups and unsaturated double bonds, which may include but are not limited to 2-propyleneamine-2-methylpropane sulfonic acid, maleic acid, fumaric acid and / or other suitable water-soluble monomers. In other embodiments, other hydrophilic monomers having unsaturated double bonds may be selectively added to the aqueous solution of carboxylic acid-containing monomers. Other hydrophilic monomers having unsaturated double bonds may be, for example, maleic anhydride, fumaric anhydride, acrylamide, methacrylamide, dimethylaminopropyl acrylamide, and chloropropyl acrylamide trimethylammonium.

[0033] The concentration of the carboxylic acid monomer aqueous solution may be, for example, 20 to 55 weight percent, or 30 to 45 weight percent. The concentration of the carboxylic acid monomer aqueous solution within this range is easier to prepare, and the reaction heat of the subsequent free radical reaction is easier to control, and the resulting water-absorbent resin may have better mechanical properties, which is beneficial to mechanical processing.

[0034] The neutralization step of the aqueous solution of the carboxylic acid monomer can be performed using an alkaline compound. In some embodiments, the alkaline compound may include, but is not limited to, alkali metal compounds, alkaline earth compounds, other suitable alkaline compounds, or any mixture of the above compounds. In some embodiments, the alkaline compound may include an alkaline compound having a hydroxyl group, a compound having a carbonic acid group, other suitable alkaline compounds, or any mixture of the above materials. In some specific examples, the alkaline compound may include, but is not limited to, sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, sodium bicarbonate, potassium bicarbonate and / or an ammonia compound.

[0035] During the neutralization step, the alkaline compound is slowly added to the aqueous solution of the carboxylic acid group monomer, wherein the addition ratio of the alkaline compound to the carboxylic acid group monomer may be, for example, 0.80 and less than 1.00, or 0.85 to 0.95, based on volume, and the neutralization step may be performed for 1 hour to 3 hours to control the temperature of the aqueous solution containing the carboxylic acid group monomer to be 15° C. to 40° C.

[0036] After the neutralization step, part of the carboxylic acid in the obtained aqueous solution of carboxylic acid monomers forms sodium salt, potassium salt or ammonium salt, thereby affecting the dissociation of the hydrophilic group, and thus increasing the water absorption of the obtained water-absorbent resin. However, if the carboxylic acid content in the aqueous solution of carboxylic acid monomers is too low, it may destroy the structure of the obtained water-absorbent resin and reduce its water absorption. Therefore, the neutralization step needs to control the carboxylic acid content of the aqueous solution of carboxylic acid monomers.

[0037] The carboxylic acid group content in the aqueous solution of carboxylic acid group-containing monomers can be evaluated by the neutralization rate. The neutralization rate is the neutralized carboxylic acid group content in the aqueous solution of carboxylic acid group-containing monomers. Based on the carboxylic acid content of the aqueous solution of carboxylic acid group-containing monomers without the neutralization step being 100 mol percent, the neutralization rate of the aqueous solution of carboxylic acid group-containing monomers can be greater than or equal to 45 mol percent, such as: 45 mol percent to 85 mol percent, or 50 mol percent to 75 mol percent.

[0038] The carboxylic acid content in the aqueous solution of carboxylic acid monomers can also be evaluated by pH value, wherein the pH value of the aqueous solution of carboxylic acid monomers is less than or equal to 7.0, such as 5.0 to 7.0, or 5.5 to 6.5. If the pH value of the aqueous solution of carboxylic acid monomers is greater than 7.0, the water-absorbent resin obtained not only has defects such as a large amount of residual monomers and reduced water absorption, but also has the problem of easily causing skin allergies after contact with the skin. When the pH value of the aqueous solution of carboxylic acid monomers is 5.0 to 7.0, the water-absorbent resin obtained has a small amount of residual monomers and better water absorption.

[0039] The aqueous solution of carboxylic acid-containing monomers may optionally include water-soluble polymers. The molecular weight of the water-soluble polymer is not particularly limited, but it is understood that the molecular weight of the added water-soluble polymer will not affect the water absorption of the obtained water-absorbent resin. In some embodiments, the water-soluble polymer may include, but is not limited to, partially saponified or completely saponified polyvinyl alcohol, polyethylene glycol, polyacrylic acid, polyacrylamide, starch and / or starch derivatives (such as methyl cellulose, methyl cellulose acrylate and / or ethyl cellulose). In some specific examples, the water-soluble polymer may be starch and / or partially saponified or completely saponified polyvinyl alcohol.

[0040] Based on 100 weight percent of the aqueous solution of the carboxylic acid group-containing monomer, the amount of the water-soluble polymer used can be 0 weight percent to 20 weight percent, such as greater than 0 weight percent to 10 weight percent, or greater than 0 weight percent to 5 weight percent, so that the obtained water-absorbent resin has better water absorption.

[0041] Hydrolyzed collagen is obtained by hydrolyzing collagen. The source of collagen is not particularly limited, and may come from the skin, bones or cartilage of terrestrial animals such as cattle, pigs or poultry, or the skin, bones, fins, scales and / or swim bladder of aquatic animals. In some specific examples, the collagen may come from the scales of milkfish.

[0042] The hydrolysis step may include, but is not limited to, acidic hydrolysis, alkaline hydrolysis, and / or enzyme hydrolysis. For the enzyme hydrolysis method, reference may be made to the review article "Biological activity of peptides purified from fish skin hydrolysates" published by Racheal Abuine et al. in the journal "Fisheries and Aquatic Sciences" Vol. 22, No. 10 in 2019, the article "Study on the antioxidant activity of tilapia scale hydrolyzed collagen enzyme hydrolyzate" published by Lai Zhixing et al. in "Aquatic Research" on pages 99 to 108 before 2007, and patent publication No. TW 200831005A, which are listed as references here. In some embodiments, the hydrolyzed collagen may be a commercially available product, such as fish scale hydrolyzed collagen (product name: FCMB101) produced by Novon Biomedical Technology Co., Ltd.

[0043] The type of protease is not particularly limited. In some embodiments, the protease may be an endoprotease from the perspective of whether the protease acts on the end of the collagen. In some embodiments, the protease may include, but is not limited to, serine proteases, threonine proteases, cysteine ​​proteases, aspartic proteases, glutamic acid proteases and / or metalloproteases from the perspective of the amino acid classification of the activation site of the protease. In some specific examples, the protease may be alkaline protease, papain and / or bromelain. It should be noted that the alkaline protease may be a protease of Bacillus licheniformis, which is a type of serine endopeptidases.

[0044] Based on 100 weight percent of the aqueous solution of the carboxylic acid group-containing monomer, the amount of the hydrolyzed collagen used can be 0.1 weight percent to 20 weight percent, such as 0.5 weight percent to 10 weight percent, or 0.5 weight percent to 5 weight percent. When the amount of the hydrolyzed collagen used is within the above range, the water-absorbent resin obtained has high dryness and appropriate biodegradability.

[0045] The molecular weight of the hydrolyzed collagen may be, for example, greater than or equal to 1 KDa and less than 10 KDa, such as greater than or equal to 1 KDa and less than or equal to 5 KDa. When the molecular weight of the hydrolyzed collagen is within this range, the water-absorbent resin prepared may have high water absorption, high dryness and appropriate biodegradability.

[0046] After the carboxylic acid group-containing monomer aqueous solution and the hydrolyzed collagen are mixed, a crosslinking agent and a polymerization initiator are added, and a free radical polymerization reaction is carried out. The free radical polymerization reaction can be carried out in a batch reactor or in a conveyor belt reactor. After the free radical polymerization reaction, the hydrolyzed collagen can be physically dispersed in the cross-linked bridge structure.

[0047] During the free radical polymerization reaction, the crosslinking agent can make the obtained water-absorbent resin have an appropriate degree of crosslinking to form a gel, and the gel can have appropriate processability. The type of the crosslinking agent is not particularly limited, and can include a compound having at least two unsaturated double bond groups, a compound having at least two epoxy groups, other appropriate crosslinking agents, or any mixture of the above compounds. In some specific examples, the compound having at least two unsaturated double bond groups may include, but is not limited to, N,N'-bis(2-propylene)amine, N,N'-methylenebisacrylamide, N,N'-methylenebismethacrylamide, propylene acrylate, ethylene glycol diacrylate, polyethylene glycol diacrylate, ethylene glycol dimethacrylate, polyethylene glycol dimethacrylate, glycerol triacrylate, glycerol trimethacrylate, glycerol triacrylate with ethylene oxide added, glycerol trimethacrylate with ethylene oxide added, trimethylolpropane triacrylate with ethylene oxide added, trimethylolpropane trimethacrylate with ethylene oxide added, trimethylolpropane trimethacrylate, trimethylolpropane triacrylate, N,N,N-tri(2-propylene)amine, ethylene glycol diacrylate, polyoxyethylene glycerol triacrylate, diethyl polyoxyethylene glycerol triacrylate and / or dipropylene triethylene glycol ester. In some embodiments, the compound having at least two unsaturated epoxy groups may include, but is not limited to, sorbitol polyglycidyl ether, polyglycerol polyglycidyl ether, ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether and / or diglycerol polyglycidyl ether.

[0048] Based on 100 parts by weight of the solid content of the water-absorbent resin composition, the amount of the crosslinking agent used can be, for example, 0.001 parts by weight to 5 parts by weight, such as 0.01 parts by weight to 3 parts by weight. When the amount of the crosslinking agent used is within the above range, the mechanical properties of the formed gel are better, which is conducive to mechanical processing.

[0049] The polymerization initiator can decompose to generate free radicals, thereby inducing the aforementioned free radical polymerization reaction, thereby forming a gel. The polymerization initiator of the present invention may include, but is not limited to, a thermal decomposition type initiator, a redox type initiator, other appropriate polymerization initiators, or any mixture of the above materials. In some specific examples, the redox type initiator may include acidic sulfites, thiosulfates, ascorbic acid or ferrous salts, sodium bisulfate and / or ammonium persulfate. In some specific examples, the thermal decomposition type initiator may include hydrogen peroxide (i.e., hydrogen peroxide), di-tert-butyl peroxide, peroxide amide, persulfate (such as ammonium salt or alkali metal salt, etc.) and / or azo compounds (such as: 2,2'-azobis(2-amidinopropane) dihydrochloride or 2,2'-azobis(N,N-dimethylisobutylamidine) dihydrochloride, etc.).

[0050] When the polymerization initiator contains both a thermal decomposition type initiator and a redox type initiator, the redox type initiator can first decompose to generate free radicals, thereby inducing the first stage of free radical polymerization. At the same time, the reaction heat generated by the first stage of free radical polymerization can decompose the thermal decomposition type initiator, thereby inducing the second stage of free radical polymerization, thereby increasing the reactivity of the free radical polymerization reaction.

[0051] Based on 100 weight percent of the neutralized carboxylic acid monomer compound, the amount of the polymerization initiator used is 0.001 weight percent to 10 weight percent, such as 0.1 weight percent to 5 weight percent. When the amount of the polymerization initiator used is 0.001 weight percent to 10 weight percent, the free radical polymerization reaction can have appropriate reactivity, and the water-absorbent resin obtained can be prevented from forming a solid rather than a gel due to excessive polymerization.

[0052] After the free radical polymerization reaction, a drying step is further performed to obtain a water-absorbent resin. The drying step can effectively remove moisture and residual monomers in the gel. Therefore, compared with the water-absorbent resin without the drying step, the water-absorbent resin obtained by drying has better water absorption. In some embodiments, the temperature of the drying step can be, for example, 100° C. to 180° C., and the temperature of the drying step can be, for example, 1 hour to 3 hours, so as to effectively remove moisture and residual monomers in the water-absorbent resin and control the crosslinking degree of the water-absorbent resin.

[0053] Before the drying step is performed, the gel body may be subjected to a crushing step to obtain a gel block. In some embodiments, the crushing step may be performed using a cutting grinder. The diameter of the gel block may be, for example, less than or equal to 2.0 mm, or 0.03 mm to 1.5 mm. Gel blocks with a diameter within the above range have better thermal conductivity and fine powder content, which can be beneficial for removing residual monomers and moisture, and can avoid increasing the production cost of subsequent processing. It is worth noting that the narrower the particle size distribution of the gel block, the better the efficiency of the drying step, and the better the water absorption of the resulting dried product.

[0054] After the drying step, the water-absorbent resin is further crushed and sieved to obtain water-absorbent resin powder, wherein the diameter of the water-absorbent resin powder can be, for example, 0.06 mm to 1.00 mm, or 0.10 mm to 0.85 mm, to achieve a better fine powder amount and water absorption.

[0055] After the free radical polymerization and drying steps, the obtained water-absorbent resin has a uniform cross-linked bridge structure, so the water-absorbent resin is an insoluble hydrophilic polymer. In order to further increase the water absorption properties of the water-absorbent resin, such as the absorption rate, colloid strength, anti-caking and liquid permeability, the water-absorbent resin can be selectively subjected to surface cross-linking treatment to further bridge the surface of the water-absorbent resin. The surface cross-linking treatment includes mixing the surface treatment agent and the water-absorbent resin, and heat-treating at 140°C to 160°C for 0.5 to 1.5 hours.

[0056] The surface treatment agent used for the surface cross-linking treatment may include, but is not limited to, a multifunctional cross-linking agent that can react with a carboxylic acid group. In some embodiments, the surface treatment agent may include, but is not limited to, a polyol, a polyamine, a compound having at least two epoxy groups, an alkylene carbonate, other appropriate cross-linking agents, or any combination of the above materials. In some specific examples, the surface treatment agent may include, but is not limited to, glycerol, ethylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, propylene glycol, 1,4-butanediol, ethylenediamine, diethylenediamine, triethylenediamine, sorbitol polyglycidyl ether, polyglycerol polyglycidyl ether, ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, diglycerol polyglycidyl ether, ethylene glycol carbonate, 4-methyl-1,3-dioxolan-2-one, 4,5-dimethyl-1,3-dioxolan-2-one, 4,4-dimethyl-1,3-dioxolan-2-one, 4-ethyl-1,3-dioxolan-2-one, 1,3-dioxan-2-one, 4,6-dimethyl-1,3-dioxan-2-one and / or 1,3-dioxepan-2-one.

[0057] Based on 100 parts by weight of the water-absorbent resin composition, the amount of the surface treatment agent used may be, for example, 0.001 to 10 parts by weight, preferably 0.005 to 5 parts by weight, to achieve a suitable crosslinking effect and increase the water absorbency of the obtained water-absorbent resin.

[0058] Depending on the form of the surface treatment agent, the surface treatment agent can be directly added to the water-absorbent resin composition, or first prepared into a cross-linking solution and then added to the water-absorbent resin composition. The cross-linking solution can be water or a hydrophilic organic solvent (e.g., methanol, ethanol, propanol, isobutyl alcohol, acetone, methyl ether and / or ethyl ether). In some embodiments, the hydrophilic organic solvent is preferably methanol or ethanol.

[0059] In some specific examples, the absorbent resin prepared by the present invention can be applied to sanitary products such as diapers (e.g., Fluffless diapers (using a large amount of absorbent resin) or adult diapers), so that the diapers have high water absorbency, high dryness and appropriate biodegradability.

[0060] In some application examples, the water-absorbent resin can be used to manufacture an absorbent body. The absorbent body can be made by mixing the water-absorbent resin and a fiber substrate. Generally speaking, the basis weight (unit area weight) of the absorbent body can be 0.01 g / cm 2 Up to 0.30g / cm 2 , and the thickness of the absorbent body is not more than 30mm.

[0061] In some embodiments, the fiber substrate may be a hydrophilic fiber to facilitate the diffusion and transfer of liquid, thereby increasing the water absorption of the absorbent. In some specific examples, the hydrophilic fiber may include but is not limited to pulverized wood pulp.

[0062] In some embodiments, based on the weight of the absorbent body being 100 weight percent, the weight of the water-absorbent resin is greater than or equal to 20 weight percent and less than 100 weight percent, such as greater than or equal to 40 weight percent and less than 100 weight percent, or greater than or equal to 50 weight percent and less than 100 weight percent.

[0063] In actual applications, the absorbent body may be disposed on a liquid-impermeable polyethylene film, and a liquid-permeable nonwoven fabric may be disposed on the absorbent body to form a composite layer structure. Depending on the application requirements, in other application examples, the composite layer structure may not include a fiber substrate. In other words, the water-absorbent resin is directly disposed on the polyethylene film, and the nonwoven fabric is disposed on the water-absorbent resin. In these application examples, the water-absorbent resin laid between the polyethylene film and the nonwoven fabric is not tightly stacked, so that the water-absorbent resin has space to expand and can absorb liquid more effectively.

[0064] Several embodiments are used below to illustrate the application of the present invention, but they are not used to limit the present invention. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention.

[0065] Preparation Example 1

[0066] 540 g of acrylic acid and 583 g of water were mixed to obtain an acrylic acid aqueous solution. Then, 437.5 g of a sodium hydroxide aqueous solution with a concentration of 48 weight percent was added dropwise to the acrylic acid aqueous solution to perform a neutralization step. The ratio of sodium hydroxide to acrylic acid was 0.85 to 0.95, the time of the neutralization step was 2 hours, and the temperature of the acrylic acid aqueous solution was 15° C. to 40° C. during the neutralization step. After the neutralization reaction, an acrylic acid aqueous solution with a monomer concentration of 42 weight percent was obtained, in which 70 mole percent of acrylic acid was neutralized to sodium acrylate, and the acrylic acid aqueous solution had a pH of 5.71.

[0067] Next, an acrylic acid aqueous solution and 15.60 g of hydrolyzed collagen with a molecular weight of 1500 g / mol (product name: FCMB101; manufacturer: Novo Biomedical Technology Co., Ltd.) were added, mixed, and then 0.9 g of N,N'-methylenebisacrylamide was added, and the temperature was kept at about 20°C. Then, 3.6 g of sodium bisulfite, 3.6 g of ammonium persulfate, and 0.3 g of hydrogen peroxide were added to perform a free radical polymerization reaction to obtain a gel. The gel was crushed using a shear mill to obtain a gel block with a particle size of less than or equal to 2.0 mm.

[0068] Next, the gel block was dried at 130°C for 2 hours, and then sieved using a 0.10 mm to 0.85 mm sieve to obtain a powder. Next, 200 g of the powder was added to 5 g of a surface treatment agent and an organic solvent, and then heat-treated at 150°C for 1 hour, and allowed to stand and cool to obtain the water-absorbent resin of Preparation Example 1. The surface treatment agent solution included ethylene glycol and 1,4-butanediol (manufacturer: Taiwan Plastics Industry Co., Ltd.), and the organic solvent included methanol, wherein the volume ratio of ethylene glycol, 1,4-butanediol and methanol was 1.0:1.0:0.5.

[0069] Preparation Example 2 to Preparation Example 5, Preparation Comparative Example 1 to Preparation Comparative Example 3

[0070] The manufacturing methods of the water-absorbent resins of Preparation Examples 2 to 5 and Preparation Comparative Examples 1 to 3 are similar to Preparation Example 1, except that the amount of hydrolyzed collagen used, the molecular weight and / or the preparation method are different. Specifically, compared with the hydrolyzed collagen of Preparation Example 1, Preparation Example 2 uses 15.60 g of hydrolyzed collagen (product name: FCMB101, molecular weight 3000 g / mol); the amount of hydrolyzed collagen (product name: FCMB101) used in Preparation Example 3 is increased to 46.80 g; and the amount of hydrolyzed collagen (product name: FCMB101) used in Preparation Example 4 is reduced to 7.80 g.

[0071] The hydrolyzed collagen added to the water-absorbent resin of Preparation Example 5 is obtained by hydrolyzing fish scale collagen with commercially available alkaline protease (alcalase), and the amount used is 15.6 g. The hydrolysis step is based on the article "Study on the Antioxidant Activity of Tilapia Scale Hydrolyzed Collagen Enzyme Hydrolyzate" published by Lai Zhixing et al. in "Aquatic Research" on pages 99 to 108 before 2007, which is briefly described as follows: After the fish scale is acid-deashed, a hydrolyzing protease is added, and the hydrolysis step is carried out at 45° C. to 55° C. for 1 hour to 5 hours to obtain hydrolyzed collagen.

[0072] No hydrolyzed collagen was added to the water-absorbent resin prepared in Comparative Example 1; the amount of hydrolyzed collagen (product name: FCMB101) added to the water-absorbent resin prepared in Comparative Example 2 was reduced to 0.83 g; the hydrolyzed collagen used in the water-absorbent resin prepared in Comparative Example 3 was prepared using the method described in Preparation Example 5, but its molecular weight was 10,000 g / mol (i.e., 10 KDa).

[0073] It should be noted that the molecular weight of hydrolyzed collagen can be detected by liquid chromatography analysis, using a Superdex 30increase column, an eluent including 0.1 M sodium sulfate (Na2SO4), 0.02 M sodium dihydrogen phosphate (NaH2PO4) at pH 5.3, and 0.5% sodium dodecyl sulfate (SDS), and the flow rate of the eluent is 0.5 mL / min.

[0074] The usage amounts and molecular weights of the hydrolyzed collagens of Preparation Examples 1 to 5 and Preparation Comparative Examples 1 to 3 are recorded in Table 1.

[0075] Preparation Example 6

[0076] Using an absorbent body forming machine, 10.0 g of the water-absorbent resin obtained in Preparation Example 1 and 10.0 g of pulverized wood pulp were mixed to obtain a mixture. Next, the mixture was formed using a metal net with a mesh size of 400 mesh (i.e., a pore size of 38 μm) to obtain an absorbent body having an absorbent body area of ​​160 cm 2 (8cm×20cm). Then, the formed absorbent was placed on a polyethylene (PE) film, and then the non-woven fabric was covered on the absorbent. Next, a pressure of 18.39 kPa was applied to the absorbent (area 160 square centimeters, weight 30 kg), and after 5 minutes, the absorbent, polyethylene film and non-woven fabric were glued together with white glue to obtain the test absorbent of Preparation Example 6.

[0077] Preparation Examples 7 to 10 and Preparation Comparative Examples 4 to 6

[0078] The manufacturing methods of the test absorbent bodies of Preparation Examples 7 to 10 and Preparation Comparative Examples 4 to Preparation Comparative Examples 6 are similar to those of the test absorbent body of Preparation Example 6, the difference being that Preparation Examples 7 to 10 and Preparation Comparative Examples 4 to Preparation Comparative Examples 6 use the water-absorbent resins of Preparation Examples 2 to 5 and Preparation Comparative Examples 1 to Preparation Comparative Examples 3, respectively.

[0079] Evaluation method

[0080] The following evaluation methods were used to evaluate the absorption rate, centrifugal retention capacity, water absorption rate under pressure, water absorption rate under pressure of shell-core, absorption index under pressure, residual monomer and colloid strength of the water-absorbent resins of Preparation Examples 1 to Preparation Examples 7 and Preparation Comparative Examples 1 to Preparation Comparative Examples 3, and the results are recorded in Table 1.

[0081] Next, the rewet amount of the test absorbent bodies prepared in Preparation Examples 6 to 10 and Preparation Comparative Examples 4 to 6 was evaluated using the following evaluation method, and the results are recorded in Table 2. It is to be noted that, unless otherwise specified, the temperature of the following evaluation method is 23±2°C and the relative humidity of the air is 45±10%. Before the evaluation method is performed, the water-absorbent resin should be fully mixed.

[0082] Retention

[0083] The test method is based on ERT 441.3 (10) specified by the European Disposables and Nonwovens Association (EDANA).

[0084] Water absorption under pressure

[0085] The water absorption rate under pressure of the water-absorbent resin is evaluated according to the determination method of ERT 442.3 (10) specified by the European Nonwovens Association. The method is briefly described as follows: the initial weight of the water-absorbent resin is measured, and then a pressure of 4.9 kPa is applied to the water-absorbent resin. After the water-absorbent resin absorbs a sodium chloride aqueous solution with a concentration of 0.9 weight percent for 60 minutes, the weight of the water-absorbent resin after water absorption is measured. The water absorption rate under pressure can be obtained by dividing the weight after water absorption by the initial weight.

[0086] Water absorption rate under shell-core pressure

[0087] The evaluation method of the water absorption under pressure of the core-shell is the same as the evaluation method of the test method of the water absorption under pressure described above, but the time for the water-absorbent resin to absorb the sodium chloride aqueous solution is longer (240 minutes).

[0088] Absorption index under pressure

[0089] The ratio of the water absorption rate under pressure of the shell core to the water absorption rate under pressure was calculated to obtain the absorption index under pressure.

[0090] Residual monomer

[0091] The residual monomers of the water-absorbent resin were evaluated according to the measurement method of ERT 410.3 (10) specified by the European Nonwovens Association.

[0092] Absorption rate

[0093] The absorption capacity of the water-absorbent resin was evaluated according to the measurement method of ERT 420.3 (10) specified by the European Nonwovens Association.

[0094] Colloid strength

[0095] 1.000±0.001 g of water-absorbent resin was slowly added to 30 mL of physiological saline solution, stirred for 1 minute using an electromagnetic stirrer and allowed to stand for 3 hours or 24 hours, and then the colloid strength of the water-absorbent resin was tested using a STEVENS colloid strength tester, wherein the physiological saline solution contained 0.005 weight percent of L-ascorbic acid, and the STEVENS colloid strength tester was set to a drop speed of 1.0 mm / sec and a drop distance of 25 mm for the suspension column.

[0096] Back infiltration

[0097] Prepare 30 filter papers, each of which is 8 cm x 20 cm in size, and measure the initial weight (W1) of the 30 filter papers. 2 A weight is uniformly applied to the test absorbent body to apply a pressure of 4.8 kPa, and 180 mL of synthetic urine is dripped onto the center point of the test absorbent body three times, each time at an interval of 30 minutes, wherein the synthetic urine is as described in U.S. Patent No. 20040106745. Next, the weight on the test absorbent body is removed, and the 30 filter papers are placed on the test absorbent body, and then the weight is immediately placed on the 30 filter papers, and the filter papers absorb the re-infiltrated liquid for 5 minutes, and then the weight (W2) of the 30 filter papers after absorption is measured. The difference between the weight (W2) of the 30 filter papers after absorption and the initial weight (W1) is calculated to obtain the re-infiltration amount of the test absorbent body to the synthetic urine.

[0098] Evaluation results

[0099] Table 1

[0100]

[0101] Table 2

[0102]

[0103] As shown in Table 1, the water absorption rate under pressure of the water-absorbent resins of Preparation Examples 1 to 5 is greater than 15 g / g, the absorption rate under pressure is greater than or equal to 0.8, and the re-permeation amount of the prepared test absorbent is less than or equal to 3 g, indicating that the water-absorbent resin still has good water absorption after adding hydrolyzed collagen.

[0104] Secondly, as shown in Table 1, after being treated with L-ascorbic acid for 3 hours and 24 hours, the colloid strength of the water-absorbent resins of Preparation Examples 8 to Preparation Examples 12 is indeed lower than that of Preparation Comparative Examples 1 to Preparation Comparative Examples 3, indicating that the addition of hydrolyzed collagen in an appropriate amount (e.g., greater than 0.83 g) and an appropriate molecular weight (e.g., 1000 g / mol to less than 10000 g / mol) can produce water-absorbent resins with better biodegradability.

[0105] Furthermore, compared with Comparative Examples 4 to 6, the rewet amount of the test absorbent bodies of Examples 8 to 12 is lower, indicating that the absorbent body made by using the water-absorbent resin with added hydrolyzed collagen is still not easy to release the absorbed liquid after being subjected to external pressure, and is dry and comfortable to use.

[0106] Next, according to the evaluation results of the colloid strength shown in Table 1, it can be seen that the colloid strength of the water-absorbent resin of the present invention is significantly reduced after being immersed in L-ascorbic acid for 3 hours or 24 hours, and it has good biodegradability.

[0107] As can be seen from the above embodiments, the water-absorbent resin composition and the method for producing the water-absorbent resin of the present invention have the advantages that by adding hydrolyzed collagen, a water-absorbent resin with high water absorbency, high dryness and appropriate biodegradability can be produced, which can be applied to personal hygiene products such as baby diapers, female sanitary products, disposable wipes or adult diapers, or can be applied to agriculture and horticulture, construction, petroleum industry, cable manufacturing, medicine and entertainment, etc.

[0108] Although the present invention has been disclosed as above with several specific embodiments, various modifications, changes and substitutions may be made to the aforementioned disclosure, and it should be understood that in some cases, certain features of the embodiments of the present invention will be adopted but other features will not be used accordingly without departing from the spirit and scope of the present invention. Therefore, the spirit and scope of the claims of the present invention should not be limited to the above exemplary embodiments.

Claims

1. A water-absorbent resin composition, characterized in that include: An aqueous solution of a carboxylic acid-containing monomer, wherein the neutralization rate of the aqueous solution of the carboxylic acid-containing monomer is greater than or equal to 45 mol%, and the pH value of the aqueous solution of the carboxylic acid-containing monomer is less than or equal to 7.0; Hydrolyzed collagen; Cross-linking agent; as well as The polymerization initiator includes a thermal decomposition type initiator and / or a redox type initiator.

2. The water-absorbent resin composition according to claim 1, characterized in that The molecular weight of the hydrolyzed collagen is greater than or equal to 1 KDa and less than 10 KDa.

3. The water-absorbent resin composition according to claim 1, characterized in that Based on 100 weight percent of the water-absorbent resin composition, the amount of the hydrolyzed collagen used is 0.1 weight percent to 20 weight percent.

4. The water-absorbent resin composition according to claim 1, characterized in that Also included are surface treatment agents.

5. The water-absorbent resin composition according to claim 1, characterized in that The hydrolyzed collagen is prepared by hydrolyzing fish scales with a hydrolyzing protease.

6. The water-absorbent resin composition according to claim 1, wherein Wherein the hydrolytic protease is a serine endoprotease.

7. A method for producing a water-absorbent resin, characterized in that: include: A step of neutralizing the carboxylic acid monomer aqueous solution with an alkaline compound to obtain a carboxylic acid monomer aqueous solution, wherein the neutralization rate of the carboxylic acid monomer aqueous solution is greater than or equal to 45 mol percent, and the pH value of the carboxylic acid monomer aqueous solution is less than or equal to 7.0; Mixing the carboxylic acid group-containing monomer aqueous solution, hydrolyzed collagen, a cross-linking agent and a polymerization initiator to perform a free radical polymerization reaction, wherein the hydrolyzed collagen is obtained by hydrolyzing fish scales with a hydrolyzing protease; and After the radical polymerization reaction is performed, a drying step is performed to obtain the water-absorbent resin.

8. The method for producing a water-absorbent resin according to claim 7, wherein: The method further comprises subjecting the water-absorbent resin to a surface cross-linking treatment.

9. The method for producing a water-absorbent resin according to claim 7, wherein: Wherein the hydrolytic protease is a serine endoprotease.

10. The method for producing a water-absorbent resin according to claim 7, wherein: The molecular weight of the hydrolyzed collagen is greater than or equal to 1 KDa and less than 10 KDa.

Citation Information

Patent Citations

  • Biodegradable water-absorbing resin

    JP1999343339A

  • A making method for extracting collagen peptides from fish scales

    TW200831005A

  • Water-absorbing agent and production process therefor, and sanitary material

    US20040106745A1

  • Modified biopolymers and methods of producing and using the same

    US20170002098A1